Power and Piety: The Discourse of Hegemony in the History of Christian Mission and Colonialism in Asia - Gaol, Ebeneser Lumban (East Asian Journal of Multidisciplinary Research, 2025)
This paper examines the complex role of Christian missions in Asia from the 16th to the 20th century through Antonio Gramsci’s theory of hegemony. Using a qualitative research method and literature study technique, the research concludes that missionaries served both as evangelists and instruments of Western cultural hegemony, supporting colonial power structures. While promoting colonial dominance, missionaries also created spaces for counter-hegemony by establishing educational institutions and social services, empowering local communities with knowledge to resist colonialism. Gramsci’s theory of hegemony helps reveal how missionaries facilitated interactions between colonial power and colonized societies. These interactions contributed to a process that not only supported colonial domination but also challenged it.